PENINGKATAN BIOMASSA NANNOCHLOROPSIS OCULATA MELALUI OPTIMASI KULTUR PADA SKALA LABORATORIUM DAN SKALA MENENGAH - Munru, Maestro; Wulandari, Yola; Sari, Herni Iman; Syafitri, Novita nanda; Maulana, Alfiqi; Ayu, Trifajriyah Lutea (Program Studi Akuakultur, Universitas Bangka Belitung, 2025)
Nannochloropsis oculata, a versatile microalga, holds immense potential in the field of marine biotechnology. Its benefits are far-reaching, particularly in sectors like aquaculture. To fully exploit this potential, effective strategies for increasing its biomass are essential. This study aims to determine the technique of laboratory-scale Nannochloropsis Oculata phytoplankton culture, as well as the phases of its growth and development. The culture process, spanning from 200 ml to 40 L, was Meticulously observed and documented. Daily observations were made from the first day of culture until the research was completed, using a haemacytometer on a binocular microscope with a magnification of 400. The observation results of Nannochloropsis oculata growth showed varying dynamics from the first to the fifth day. Overall, no significant growth was observed; however, fluctuations were noted in each phase of the growth period during the study. In 200 ml and 1 L volume cultures, Nannochloropsis oculata showed a short lag phase (1-2 days) followed by a significant increase in biomass up to 11 million cells/ml in the exponential phase (days 3 to 5). Controlled and stable conditions at small volumes favored cell adaptation and optimal replication. In contrast, the 15 L volume culture showed a more extended lag phase, indicating sensitivity to environmental changes. The most significant anomaly occurred in the 40 L culture, where a drastic decrease in biomass occurred after the second to third day, signaling culture failure. Microscopic analysis confirmed protozoan contamination as the etiological agent, which was assumed to originate from the surrounding environment due to exposure to the culture medium.